Pengaruh Pemberian Ekstrak Etil Asetat Buah Biwa (Eriobotrya japonica (Tunb.) Lindl) Terhadap Profil Mikrobiota Usus Tikus Yang Diinduksi Escherichia coli - Diana Intan Gabriella Lusiana; Yesiska Kristina Hartanti; Pangeran Andareas; Justina Andrea Renjaan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study investigated the therapeutic potential of ethyl acetate extract derived from Biwa fruit on the gut microbiota profile of E. coli-infected mice. This study used 30 BALB-C mice divided into five groups: positive control (Ciprofloxacin and Lomperamide 130 mg/kgBW), negative control (CMC-Na), and three Biwa extract treatment groups at doses of 200, 400, and 600 mg/kgBW. The findings demonstrated that Biwa extract at 200 mg/kgBW exhibited significant efficacy from day one, resulting in complete suppression of E. coli growth in mice. However, the cohort receiving 400 mg/kgBW showed recurring E. coli growth on day two, potentially attributable to contamination. This research provides promising preliminary evidence of the potential of Biwa fruit as an alternative herbal-based prebiotic therapy to overcome E. coli infection.